Assessing UK patients' knowledge of anaesthetists and anaesthesia - Oliver J.H. Baker; Rama Varadan (BJA Open)
Background: Previous UK studies found that only 50–67% of patients are aware that anaesthetists are qualified doctors, and public knowledge of anaesthetists' roles was poor. This study aimed to assess patients' knowledge of anaesthetists and anaesthesia, to identify if there has been any improvement over the past two decades. A secondary aim was to determine if exposure to anaesthetists during day case surgery improved patient knowledge. Methods: This UK-based, single-centre, cross-sectional study included 150 patients attending for day case surgery. Patients were given a questionnaire on their knowledge of anaesthetists and anaesthesia both before and after surgery. Patients were included if they had not yet been pre-assessed by an anaesthetist, if they were over 18 years old and if they were not healthcare professionals. Results: All 150 patients completed both preoperative and postoperative questionnaires. 51.3% were female and the median age was 51.6 years (range 18–90 years). Before surgery, only 39.3% of patients knew that anaesthetists were doctors, despite 82.4% having had previous anaesthetics. After surgery, this reduced to 38%. There was no significant improvement in patients' knowledge of anaesthetists’ roles both inside and outside of operating theatres in postoperative questionnaires (p>0.05). Patients most frequently recognised that anaesthetists work in operating theatres (80%), intensive care units (54%), medical emergency teams (52.7%), and on labour wards (50%). Furthermore, 76.6% of patients recalled seeing an anaesthetist before previous operations and 81.3% were aware that general anaesthesia involved volatile gases or intravenous drugs. Conclusions: This study found that many patients are not aware that anaesthetists are medically qualified. Exposure to anaesthetists on the day of surgery did not improve patients' knowledge of the roles of anaesthetists or their knowledge of anaesthesia itself.